kauppahalli - Schlüterin Kirjakauppa Yhtiö
fyysinen kuvaus: vaaka
Keywords: kauppahallit; naisten puvut; rattaat; mukulakivet; katukivet; Suomi, Joensuu, Joensuun kauppahalli, Joensuu, Joensuun kauppahalli